2003
DOI: 10.1097/01.blo.0000093842.72468.73
|View full text |Cite
|
Sign up to set email alerts
|

Critical Evaluation of Mirels??? Rating System for Impending Pathologic Fractures

Abstract: This project examined the hypothesis that Mirels' rating system for impending pathologic fractures is reproducible, valid, and applicable across various experience levels and training backgrounds. Twelve true clinical histories and corresponding radiographs for patients with femoral metastatic lesions were reviewed by 53 participants from five experience levels: orthopaedic residents, musculoskeletal radiologists, orthopaedic attendings, fellowship-trained practicing orthopaedic oncologists, and radiation or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
102
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(105 citation statements)
references
References 4 publications
2
102
0
1
Order By: Relevance
“…With the use of this risk-stratification tool, surgeons are able to determine accurately which pathologic lesions are prone to fracture and based on that, surgeons can decide which lesions to treat prophylactically with surgery. Prior retrospective studies have suggested many benefits of prophylactic surgical treatment of impending fractures compared with treatment of realized pathologic fractures, including less blood loss, less operative morbidity, and an improved likelihood of early mobilization [6,20]. Although the clinical benefits of prophylactic stabilization have been well established, no studies to our knowledge, have provided a cost analysis comparing costs of this treatment option with the costs of providing care to patients after pathologic fractures have occurred.…”
Section: Introductionmentioning
confidence: 99%
“…With the use of this risk-stratification tool, surgeons are able to determine accurately which pathologic lesions are prone to fracture and based on that, surgeons can decide which lesions to treat prophylactically with surgery. Prior retrospective studies have suggested many benefits of prophylactic surgical treatment of impending fractures compared with treatment of realized pathologic fractures, including less blood loss, less operative morbidity, and an improved likelihood of early mobilization [6,20]. Although the clinical benefits of prophylactic stabilization have been well established, no studies to our knowledge, have provided a cost analysis comparing costs of this treatment option with the costs of providing care to patients after pathologic fractures have occurred.…”
Section: Introductionmentioning
confidence: 99%
“…The rating scheme published by Mirels [10] has been most widely adopted and uses information on radiographic evidence of bone destruction, anatomic location, pain, and lesion type to generate a composite score. However, Damron et al [2] concluded that while the Mirels' rating system ''would seem the best system available at this time…it is by no means a perfect solution to pathologic fracture risk prediction.'' The most serious problem with the Mirels system is its low specificity (33% in the original report by Mirels, 35% in the study by Damron et al [2]).…”
Section: Introductionmentioning
confidence: 99%
“…However, Damron et al [2] concluded that while the Mirels' rating system ''would seem the best system available at this time…it is by no means a perfect solution to pathologic fracture risk prediction.'' The most serious problem with the Mirels system is its low specificity (33% in the original report by Mirels, 35% in the study by Damron et al [2]). Approximately two-thirds of patients are therefore going to undergo unnecessary internal fixation procedures with strict application of these criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Mirels' classification system for impending pathologic fracture has been confirmed in two studies: (1) intramurally by Mirels [12] (78 lesions) and (2) extramurally in a study conducted by Damron et al [5] (12 lesions).…”
Section: Confirmation/validationmentioning
confidence: 81%
“…Damron et al [5] performed an evaluation to determine the reproducibility, validity, and applicability across various experience levels and training backgrounds of physicians (53 physicians). The individual Mirels' score component that showed the greatest variability was pain because of its subjective nature.…”
Section: Confirmation/validationmentioning
confidence: 99%